2005
DOI: 10.1088/0954-3899/31/8/023
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of extensive air showers with respect to the shower age

Abstract: Using CORSIKA simulations of the highest energy extensive air showers we show that all showers are similar when described by the shower age parameter: the angular and energy spectra of electrons at a given level in the atmosphere depend only on the shower age at this level. Moreover, electrons with a given energy have the same angular distributions at any level (age) of the shower. We have calculated these distributions and found analytical functions describing them quite well. The total number of particles ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 9 publications
2
59
0
3
Order By: Relevance
“…on the age parameter s [8]; it does not depend on primary particle mass or energy (the same conclusion was obtained by Nerling et al [10]), -the angular distribution of electrons with a fixed energy depends on this energy only -it is the same anywhere in the shower [9]; from the two statements above it follows that the angular distribution of all electrons (with any energy) depends on the shower age only, -the lateral distribution of electrons, if distances are expressed in the Molière unit r M at the level in consideration, depends on the shower age only [14] (the same holds for electrons with a fixed energy [19]). …”
Section: The General Ideasupporting
confidence: 67%
See 3 more Smart Citations
“…on the age parameter s [8]; it does not depend on primary particle mass or energy (the same conclusion was obtained by Nerling et al [10]), -the angular distribution of electrons with a fixed energy depends on this energy only -it is the same anywhere in the shower [9]; from the two statements above it follows that the angular distribution of all electrons (with any energy) depends on the shower age only, -the lateral distribution of electrons, if distances are expressed in the Molière unit r M at the level in consideration, depends on the shower age only [14] (the same holds for electrons with a fixed energy [19]). …”
Section: The General Ideasupporting
confidence: 67%
“…We show here that due to the similarity of high energy showers [8,9,14] it is possible to calculate the lateral distribution of ChL (LDCh) without time-consuming shower simulations, but in an analytical way (with numerical calculations of integrals), using the various earlier determined electron distributions which are universal.…”
Section: The Methods Of Calculation Of the Lateral Distribution Of Chlmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that two extra parameters are needed for the full description of the general profiles, but there can be strong correlations between them [6,7]. A widely use, successful parametrization is the GaisserHillas profile [8], which can be written in terms of the new variables, X , N , as follows:…”
Section: Shower Profile Shape Variablesmentioning
confidence: 99%